Food Data Collection in Household Consumption and Expenditure Surveys : Guidelines for Low- and Middle-Income Countries - FAO; World Bank (Rome: FAO, 2019)
Food constitutes a key component of a number of fundamental welfare dimensions, such as food security, nutrition, health, and poverty. It makes up the largest share of total household expenditure in low-income countries, accounting, on average, for about 50 percent of the household budget (United States Department of Agriculture, 2011), and accordingly, constitutes a sizeable share of the economy. Proper measurement of food consumption is, therefore, central to the assessment and monitoring of various dimensions of well-being of any population, and hence of interest to multiple international, national, and local agencies, and to several development domains – social, economic, and human. The main vehicle used to collect information on food consumption for these purposes are household consumption and expenditure surveys (HCES). However, current practices for collecting consumption data differ widely across types of surveys, between countries, and over time, compromising the quality and comparability of resulting data and measures. In the interest of improving food consumption measures and to ensure that data collected respond to the needs of a wide range of users, several development partners have come together around a common agenda aimed at harmonizing practices and recommendations for design of food consumption modules in HCES. In the present report, a preliminary set of internationally agreed recommendations to adopt in future HCES is proposed in order to collect food data aimed at improving the measurement of food consumption.